Hubungan Kecemasan dengan Keluhan Premenstrual Syndrome (PMS) pada Mahasiswi di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa Tahun Angkatan 2020 - Yunita Carolina Ero Atu; Putu Asih Primatanti; Anak Agung Gede Indraningrat (Aesculapius Medical Journal, 2023)
Menstruation is a natural process that occurs in every woman, which is a sign that the function ofthe reproductive organs has matured. Indications of premenstrual syndrome including physical,psychological and anxiety are the most common indications experienced by women when facingPMS. The purpose of the study was to determine the correlation between anxiety and premenstrualsyndrome (PMS) complaints that occurred in female students at the Faculty of Medicine andHealth Sciences at Warmadewa University, especially in the class of 2020. The type of research isanalytical observational, cross-sectional approach with a sample of 63 people. In this study, theresults obtained are the average majority of female students who have a tendency to anxiety with asevere category of 24 people or with a percentage of 38.1% and there is a frequency of 43 PMSfemale students or with a percentage of 68.3% where this shows the majority in the study. Theseare female respondents who complain of PMS. According to the results of the study, it can beconcluded that there is a correlation between anxiety and PMS complaints by students of theFaculty of Medicine and Health Sciences at Warmadewa University, especially in the class of2020 with a p value of < 0.05.